Perceptions of contraceptives as factors in birth outcomes and menstruation patterns in a rural community in Siaya county, Western Kenya - George O Onyango; George Ayodo; Nadia Smith- Diamond; Salome Wawire (Inishmore Laser Scientific Publishing Ltd, 2020)
Unmet need for contraception persists in Kenya despite an increase in awareness and availability of family planning services. There is a dearth of information on experiences and perceptions of contraception, specifically related to birth outcomes and menstruation patterns, in western Kenya. The aim of this study was to explore knowledge and perceptions on contraception, menstruation, and birth outcomes. In-depth interviews were conducted with 45 respondents; adolescent girls with children, mothers over age 20, and fathers. Six Focus Group Discussions were held with 60 participants drawn from Skilled Birth Attendants, Traditional Birth Attendants, and Community Leaders. A thematic content analysis approach was used. We found that most participants knew about contraceptives and accessed the services in their local health facilities. A majority of the women associated problems with the inability to track menstruation with contraceptive side effects. Beliefs linking contraceptives to the occurrence of preterm and birth defects were also reported among the respondents. Overall, most women approved of contraceptives, however, perceptions remained largely negative among men. While contraception remains an important health service for improvement of maternal-child health, the belief that it affects menstruation and contributes to preterm births hinders its uptake in the community. There should be programmatic intervention targeting families to change the negative perceptions linked to contraceptive use.